Spatial and temporal variability of depth and density of the snow cover in Russia - N. I. Osokin; A. V. Sosnovsky (Лëд и снег, 2015)
Measurements of snow cover depth and density made in 2001–2010 in the snow survey routes made it possible to study spatial and temporal variability of these characteristics on the territory of Russia. Maps of distribution of the snow cover depth and density in November, January and March for this period were constructed. Comparison of these maps with similar ones for the period from 1966 to 2000 did show that in November of the last years, significant (up to 40%) reduction in snow cover depth took place on the north-east of the European part in the river Pechora basin, in central regions of the West Siberia, and in north-east Siberia. As compared to the data of 1966–2000 the maximal snow depth for the period of 2001–2010 increased by 40% on the north of the Tyumen oblast, and in some regions on the south of West Siberia as well as of the European territory. In these areas, thickness of the seasonally melted layer of soil may increase for two reasons, i.e. due to the climate warming or as a result of worse conditions for the soil freezing when snow cover depth increases. In other regions, namely, the Northern Yakutia and areas on the east of the Lena River, as well as in central regions of the West Siberia maximal snow cover depth decreased by almost 15%. Growth of maximal density of the snow cover in the years of 2001–2010 relative to that in 1966–2000 does not exceed 6%. But in the Lena river basin decrease of the snow cover maximal density was noted more significant, namely by 20%. Inhomogeneous spatial variations of the snow cover during the period 2001–2010 relative to those of 1966–2000 could result in different spatial changes in thermal conditions for the existence of permafrost and seasonally frozen ground in Russia.